What is fiction for? : literary humanism restored - Harrison, Bernard, 1933- (Indiana University Press, 2015)
"How can literature, which consists of nothing more than the description of imaginary events and situations, offer any insight into the workings of "human reality" or "the human condition"? Can mere words illuminate something that we call "reality"? Bernard Harrison answers these questions in this profoundly original work that seeks to re-enfranchise reality in the realms of art and discourse. In an ambitious account of the relationship between literature and cognition, he seeks to show how literary fiction, by deploying words against a background of imagined circumstances, allows us to focus on the roots, in social practice, of the meanings by which we represent our world and ourselves. Engaging with philosophers and theorists as diverse as Wittgenstein, Sartre, Merleau-Ponty, Foucault, Derrida, F.R. Leavis, Cleanth Brooks, and Stanley Fish, and illustrating his ideas through readings of works by Swift, Woolf, Appelfeld, and Dickens, among others, this book presents a systematic defense of humanism in literary studies, and of the study of the Humanities more generally, by a distinguished scholar"--